2017
DOI: 10.1186/s12860-017-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

ULK1 phosphorylates Sec23A and mediates autophagy-induced inhibition of ER-to-Golgi traffic

Abstract: BackgroundAutophagy is an inducible autodigestive process that allows cells to recycle proteins and other materials for survival during stress and nutrient deprived conditions. The kinase ULK1 is required to activate this process. ULK1 phosphorylates a number of target proteins and regulates many cellular processes including the early secretory pathway. Recently, ULK1 has been demonstrated to phosphorylate Sec16 and affects the transport of serotonin transporter at the ER exit sites (ERES), but whether ULK1 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 35 publications
(35 reference statements)
3
35
0
1
Order By: Relevance
“…This result is in line with earlier observations from a kinome-wide RNAi screen where ULK1 was identified as a potential regulator of ERES [20]. Contrary to its effect on Sec16A, ULK1 was shown also to phosphorylate Sec23A mainly under conditions of active autophagy [33]. This resulted in a morphologic change of ERES under amino acid starvation leading to a disrupted interaction of Sec23A with Sec31A and inhibition of protein transport.…”
Section: Nutrient Deprivation Signalingsupporting
confidence: 91%
“…This result is in line with earlier observations from a kinome-wide RNAi screen where ULK1 was identified as a potential regulator of ERES [20]. Contrary to its effect on Sec16A, ULK1 was shown also to phosphorylate Sec23A mainly under conditions of active autophagy [33]. This resulted in a morphologic change of ERES under amino acid starvation leading to a disrupted interaction of Sec23A with Sec31A and inhibition of protein transport.…”
Section: Nutrient Deprivation Signalingsupporting
confidence: 91%
“…Recently, it has been shown that, in presence of nutrients, the basal activity of ULK1 mediates the phosphorylation of SEC16A (promoting the assembly of COPII complexes at the ERES) and that, in response to starvation, the activation of ULK1 induces the dissociation of SEC23A from SEC31A (inhibiting the secretory pathway) (Gan et al, 2017;Joo et al, 2016). Our study shows that, in the absence of nutrients, activated ULK1 promotes the phosphorylation of SEC23B on Ser186 promoting the formation of autophagic COPII vesicles.…”
Section: Discussionsupporting
confidence: 51%
“…Further regulation of COPII coat assembly is mediated by phosphorylation of Sec23 isoforms by the Unc‐51 like kinase (ULK1), an enzyme most often associated with regulating the autophagy pathway in response to nutrient availability (Figure ). When modified on sites within the trunk and β‐barrel domains of Sec23A (S207, S312 and T405), its interaction with Sec31A is dramatically reduced, suggesting that ULK1 activation impedes full COPII coat assembly required for secretory protein export from the ER, and shifts its function toward the biogenesis of donor membranes needed for autophagosome formation . ULK1 has also been shown to phosphorylate Sec23B within the trunk domain (S186) (Figure ), but in this case, phosphorylation disrupts an interaction with the F‐box protein FBXW5, which normally targets Sec23B for proteasome‐mediated degradation .…”
Section: Regulation Of Copii Carrier Formation and Transport Mediatedmentioning
confidence: 99%